The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0235816
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined associations of sleep duration and sleep quality with common physical and mental disorders: Results from a multi-ethnic population-based study

Abstract: Sleep duration and sleep quality are often linked to increased risk of mortality and morbidity. However, national representative data on both sleep duration and sleep quality and their relationship with chronic health problems are rarely available from the same source. This current study aimed to examine the independent and combined associations of sleep duration and sleep quality with physical and mental disorders, using data from the Singapore Mental Health Study 2016. 6,126 residents aged �18years participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 51 publications
3
53
0
Order By: Relevance
“…These initial studies demonstrate that 1:1 THC:CBD combination drugs provide greater symptom relief than isolates in clinical populations. It is also possible that this association could be due to known associations of mood disorders with medical conditions such as chronic pain, arthritis, sleep disturbances ( 60 62 ) and may play a mediating role between pain and sleep disturbances in arthritis patients ( 61 ). In this instance, pain may contribute to exacerbated depression symptoms in the long-term which, in turn, can result in sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…These initial studies demonstrate that 1:1 THC:CBD combination drugs provide greater symptom relief than isolates in clinical populations. It is also possible that this association could be due to known associations of mood disorders with medical conditions such as chronic pain, arthritis, sleep disturbances ( 60 62 ) and may play a mediating role between pain and sleep disturbances in arthritis patients ( 61 ). In this instance, pain may contribute to exacerbated depression symptoms in the long-term which, in turn, can result in sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Seow et al [ 70 ] studied the association of both sleep quantity and sleep quality with physical and mental disorders in Singaporean adults. Although this study used PSQI as an index to assess sleep quality, it showed that both short sleep duration and poor sleep quality were associated with chronic pain, obsessive compulsive disorders, and mental disorders.…”
Section: Quantity Versus Qualitymentioning
confidence: 99%
“…For example, studies have shown that symptoms of insomnia occur frequently among patients with cancer (Irwin, 2013), type 1 diabetes (Irwin, 2013), chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) (Mariman et al, 2013), asthma (Luyster et al, 2016), and migraine (Kim et al, 2017). Similarly, short and long sleep durations have been linked to specific illnesses such as type 2 diabetes and heart disease (Shan et al, 2015;Seow et al, 2020). Research on psychiatric disorders is hampered by the many different operationalizations of sleep problems, limiting our ability to compare how insomnia and sleep duration varies across conditions and illnesses.…”
Section: Introductionmentioning
confidence: 99%
“… Seow et al, 2020 ). Research on psychiatric disorders is hampered by the many different operationalizations of sleep problems, limiting our ability to compare how insomnia and sleep duration varies across conditions and illnesses.…”
Section: Introductionmentioning
confidence: 99%